Novel preservation state of Dolerotheca (medullosalean male organ) from the Late Pennsylvanian of the Sydney Coalfield, Nova Scotia, Canada - Zodrow, Erwin L.; Mastalerz, Maria (Atlantic Geoscience, 2019)
A new preservation state for the medullosalean male organ Dolerotheca is exemplified by a detached 31-mm sideritic mold with intact coalified compression from shale from the roof of a coal seam in the Sydney Coalfield, Cape Breton Island, Nova Scotia, Canada. Clearly recognizable in the specimen is the quadripartite campanulum. Furthermore, maceration yielded significant internal information on acellular, cuticular, stomatiferous and pubescent surfaces, and prepollen sacs with grains. Stomata are rare and of the cyclocytic type. The rectangular prepollen sacs occur as doubly paired rows of sporangia that are radially arranged, and contain ellipsoidal prepollen grains 400−520 μm long and circular prepollen grains 330−460 μm in diameter. The approximate ratio of circular to ellipsoidal grains is 1:2. Regardless of shape, the prepollen grains are attributable to the genus Monoletes. The circular grains bear vestigial trilete marks. Infrared-based functional-group chemistry distinguishes between the cover-type compression state and prepollen grains on the basis of higher aliphatic and oxygenated group contents in the grains. In summary, the specimen represents a novel state of nodular preservation with intact compression. Although the specimen is attributed to the genus Dolerotheca, specific assignment is not possible because of limited preservation and material.